2013
DOI: 10.3892/ijmm.2013.1250
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-IV as a novel gene associated with polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a common endocrine-metabolic disorder, affecting 6-10% of women of reproductive age. The etiology remains poorly understood. To investigate the differentially expressed proteins from PCOS patients versus healthy women, the protein expression in follicular fluid was analyzed using two-dimensional electrophoresis (2-DE). Since follicular fluid contains a number of secretory proteins required for oocyte fertilization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 51 publications
(54 reference statements)
2
22
1
Order By: Relevance
“…Embryo quality is associated with the presence and concentration of biomarkers in FF (Boxmeer et al., ; Hsieh, Zamah, & Conti, ; Kim et al., ). Therefore, the proteomic composition of FF from follicles can be used as an indicator of secretory activities and metabolism of follicular cells, which regulate follicle quality (Kim et al., ). Therefore, an in‐depth analysis of FF composition will likely provide a better understanding of folliculogenesis in the context of the developing microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Embryo quality is associated with the presence and concentration of biomarkers in FF (Boxmeer et al., ; Hsieh, Zamah, & Conti, ; Kim et al., ). Therefore, the proteomic composition of FF from follicles can be used as an indicator of secretory activities and metabolism of follicular cells, which regulate follicle quality (Kim et al., ). Therefore, an in‐depth analysis of FF composition will likely provide a better understanding of folliculogenesis in the context of the developing microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…FF proteome, like serum or plasma is also complex and contains dynamic ranges of proteins, thereby necessitating the use of advanced techniques which employ a gel-free approach to identify large number of proteins. Until the advent of iTRAQ based comparative approach, a few researchers used 2DE combined with MALDI-TOF/MS or nano liquid chromatographytandem mass spectrometry (LC-MS/MS) to study the FF proteomes (204,205), and identified twenty differentially expressed proteins which are involved in lipid metabolism and inflammation in PCOS. Our group has employed iTRAQ-based quantitative proteomic approach to compare the proteome of FF from women with PCOS with that of control women (160).…”
Section: Samples Used For Proteomic Studies In Pcosmentioning
confidence: 99%
“…3-hydroxyisobutyrate dehydrogenase mithocondrial HIBADH Down (211,202) Serpin family A member 1 SERPINA1 Up (160,204) Aconitase 2, mitochondrial ACO2 Up (160,222) Albumin ALB Up (209) Albumin ALB Down (160,210) Aplha-1-B-glycoprotein A1BG Up (204,205) Aplha-1-B-glycoprotein A1BG Down (160) Alpha-enolase ENO1 Down (211,212) Annexin 5 ANXA5 Up (208,210) Apolipoprotein A1 APOA1 Up (160,204) Apolipoprotein A1 APOA1 Down (208,210,222) Apolipoprotein A4 precursor APOA4 Up (204,205) Apolipoprotein C1 APOC1 Up (200) Apolipoprotein C1 APOC1 Down (160) Cathepsin D CTSD Down (211,212) Cofilin 1 CFL1 Down (211,212) F-actin capping protein alpha-1 subunit CAPZA1 Down (211,212) Fibrinogen b chain precursor FGB Up (204) Fibrinogen gamma chain precursor FGG Up (205,222) Fibrinogen, alpha chain, isoform alpha preproprotein FGA Up…”
Section: Protein Name Gene Symbol Differential Regulation Referencesmentioning
confidence: 99%
“…The present study focused on the ApoE gene promoter region and coding region to investigate the relationships between polymorphic loci and antidepressant efficacy. Apolipoprotein A4 (ApoA4) is another protein involved in lipid metabolic regulation, and has been shown to activate lecithin-cholesterol acyltransferase and cholesterylester transfer protein [24]. Data-driven analysis showed that ApoA4 has very high accuracy for discriminating individuals with remitted late-life depression (LLD) compared to never-depressed control participants [25].…”
Section: Introductionmentioning
confidence: 99%